Review: Gambaran Aktivitas Enzim Gamma Glutamyl Transferase (GGT) pada Pemain Game Online di Kecamatan Jekan Raya - Oktavia Vivin Ermanita; Ria Agustina Handayani; Eki Muharamah; Dwi Purbayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The online game is games that used an internet connection that can make players ignore sleep time. Changed sleep patterns can change circadian rhythms that cause oxidative stress which can attack liver cells. The purpose of this study was to determine the description of the activity of the enzyme Gamma Glutamyl Transferase (GGT) in Online Game players in Jekan Raya sub-district. This research was conducted by descriptive method. Population is the total of the objects that will be researched according to the characteristics desired in the study. Samples are parts that can represent the population to be used as research objects. Samples obtained in this study amounted to 50 people. The results of examination of GGT levels for online game players based on age characteristics 34.8 ± 32.3 U/L, 32.6 ± 27.1 U/L based on the characteristics of sleep duration, 28.5 ± 28.4 U/L based on the characteristics of duration playing games, 32.9 ± 28.8 U/L based on smoking activity characteristics, 42.5 ± 36.1 U/L based on blood pressure characteristics, and 29.5 ± 28.5 U/L based on body mass index characteristics (BMI). From the results of the examination of the activity of the enzyme Gamma Glutamyl Transferase (GGT) that was carried out in 50 samples there was an increase of 7 samples.